PROGRAM TERAPI ANAK AUTIS DI SLB NEGERI SEMARANG - Kurniana Bektiningsih (Universitas Negeri Yogyakarta, 2009)
ABSTRACTThe purpose of this study was to describe the programme planning, intervention, and evaluation of the instructional treatment of autistic children. Using the naturalistic qualitative approach, data were collected by interviews, observations, and document analyses. Data were validated by way of the triangulation technique, checking with department friends through discussions and by way of in-depth observation. The data collected were reduced and analysed to yield the research findings. The findings are as follows. The autism treatment programme was carried out through many steps of planning, performance, and evaluation. Autism is an integral part of children who have a special need and special education with service modelling according to their interests, needs, and abilities. Autism is a trouble and tardiness in cognitive, communication, social interaction, and habits. Autism needs a treatment programme that is the same with their education process and everything is given wholly and individually so that they can improve their abilities. Suggestions were given that autism programme be made more effective, the headmaster increase the number of teachers, and cooperation be maximalized between the school and parents.